2017
DOI: 10.7754/clin.lab.2017.170113
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Malondialdehyde Low-Density Lipoprotein Stratified by Low-Density Lipoprotein Cholesterol

Abstract: Our data indicated that high LDL-C and low HDL-C levels were independently associated with high MDA-LDL. To prevent high MDA-LDL, it is important to lower LDL-C level as well as to increase HDL-C even in subjects with low LDL-C level by lifestyle modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…We previously reported that both the MDA-LDL and sdLDL-C levels were positively correlated with the LDL-C levels 19) . Indeed, the MDA-LDL and sdLDL-C levels had a moderate to strong association with the LDL-C levels in men and women in the present study (Supplemental Fig.).…”
Section: Resultsmentioning
confidence: 94%
“…We previously reported that both the MDA-LDL and sdLDL-C levels were positively correlated with the LDL-C levels 19) . Indeed, the MDA-LDL and sdLDL-C levels had a moderate to strong association with the LDL-C levels in men and women in the present study (Supplemental Fig.).…”
Section: Resultsmentioning
confidence: 94%
“…The low density lipoprotein (LDL) is a kind of low density plasma lipoprotein, which contains about 25% protein and 49% cholesterol and cholesterol esters and can bring cholesterol into peripheral tissue cells. LDL can be oxidized into oxidized LDL by oxidants and free radicals RuiXia et al, 2020), for example, LDL extracted would be oxidized to produce MDA in the presence of oxidant ex Vivo (Moriyama & Takahashi, 2017). MDA can cause cross-linking polymerization of biomacromolecules such as protein and nucleic acid, damage nervous system and affect the function of mitochondria (Lixia et al, 2021), it is very important to inhibit the production of MDA.…”
Section: Release Rate Across Dialysis Membrane and Transdermal Experi...mentioning
confidence: 99%
“…Circulating MDA-LDL is considered to be a useful prognostic marker for future cardiac events 27) , especially in patients with low LDL-C 28) and aggressive use of LDL-lowering medications reportedly impacts MDA-LDL reduction 29) . We reported that JD consumption produced significant MDA-LDL reductions in healthy middle-aged men in a pilot study.…”
Section: Values Are Expressed As Means (95% Ci)mentioning
confidence: 99%